2020
DOI: 10.1007/s10457-020-00553-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale mammal responses to agroforestry landscapes in the Brazilian Atlantic Forest: the conservation value of forest and traditional shade plantations

Abstract: The future of tropical forest biodiversity will largely depend on human-modified landscapes. We investigated how medium- to large-bodied mammals respond to factors at local (habitat type), intermediate (land use heterogeneity, forest cover and human population density) and large spatial scales (overall forest cover) in agroforestry landscapes. We surveyed mammals using camera traps in traditional cacao agroforests (cabrucas), intensified cacao agroforests, and forest remnants within two large Atlantic Forest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
0
14
0
2
Order By: Relevance
“…By comparing different types of AF with native vegetation and other land uses, different studies [102][103][104] concluded that those AF that promoted higher disturbances in the soil caused a reduction in nitrogen contents and total soil organic carbon stocks compared to the native forest and to treatments that had less intensive soil disturbances. This effect is also demonstrated by another study [101] that concluded that those AF with higher floristic diversity registered a high concentration of soil carbon contents and stocks, increasing the quality of the added organic material, and consequently the humification processes that contribute to the longterm storage of carbon.…”
Section: Soil Qualitymentioning
confidence: 53%
See 1 more Smart Citation
“…By comparing different types of AF with native vegetation and other land uses, different studies [102][103][104] concluded that those AF that promoted higher disturbances in the soil caused a reduction in nitrogen contents and total soil organic carbon stocks compared to the native forest and to treatments that had less intensive soil disturbances. This effect is also demonstrated by another study [101] that concluded that those AF with higher floristic diversity registered a high concentration of soil carbon contents and stocks, increasing the quality of the added organic material, and consequently the humification processes that contribute to the longterm storage of carbon.…”
Section: Soil Qualitymentioning
confidence: 53%
“…Another share of these studies inferred that the positive effects of AF on soils were related to species structure and richness. By comparing different types of AF (with a different number of species) and natural vegetation as a control, these studies found better contributions for soil quality from the most diverse and rich AF than from the least diverse and rich ones [87,91,[98][99][100][101].…”
Section: Soil Qualitymentioning
confidence: 99%
“…Occupational patterns of other species were negatively associated with the basal area of small trees, which could indicate difficulty in moving and foraging in these areas (Thornton et al, 2011). However, other studies have found that vegetation traits such as vertical structure index, tree species diversity, percentage of forest and grassland (Andrade-Núñez and Aide, 2010), and forest cover (Ferreira et al, 2020) have influenced mammal species richness. Based on these studies and the fact that the occurrence of mammals can be influenced by tree fructification, we can assume that one of the reasons for the negative association between native mammals in Itatiaia National Park and mean tree basal area was due to the fact that we did not consider only fruiting trees in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Eucalyptus and Pinus ) from shaded tree plantations where native tree species, such as cocoa and coffee, grow underneath a native forest canopy. Such shaded plantations presumably favour the occurrence of wild species, given the higher vertical habitat complexity (Ferreira et al 2020). Our study also reveals an overall positive effect of exotic livestock pastures on wild ungulates, although this effect is likely to be heavily dependent on a benign landscape context.…”
Section: Discussionmentioning
confidence: 99%